Penerapan Komunikasi Persuasif Model AIDA pada Konten Instagram Komunitas Gerakan Sedekah Subuh - Alif Fadhlurrahman; Edi Wibowo (LPPM STT Terpadu Nurul Fikri, 2026)
Social media plays an essential role in building communication between social communities and the public. The Gerakan Sedekah Subuh (GSS) community, which focuses on philanthropy by distributing donations to orphans and the underprivileged, initially lacked a digital platform, limiting its ability to disseminate information and gain public trust. This study aims to identify communication challenges faced before the community had social media, design persuasive Instagram content using the AIDA model (Attention, Interest, Desire, Action), and evaluate its effectiveness in increasing brand awareness and engagement. Using a descriptive qualitative case study method, the research involved interviews, observation, and documentation, analyzed through Miles and Huberman’s model. Results show that the AIDA strategy successfully built message flow both visually and narratively. The average engagement rate reached 28.14%, with increased followers, reach, and impressions. Interviews confirm that audiences better understood GSS’s community mission and were encouraged to donate. Brand awareness reached the recognition level and tends toward brand recall.